The effect of injectable Vitamin E and trace minerals (selenium, calcium, phosphate, copper, and cobalt) on reproductive performance during non-breeding season in awassi ewes - Zonturlu, A.K.; Kacar, C.; Sönmez, M.; Yuce, A.; Kaya, S. (Russian Academy of Agricultural Sciences, 2017)
Progesterone in combination with pregnant mare serum gonadotropin (PMSG) is widely used to synchronize estrus in ewes. It is also known that various minerals and vitamins are necessary to provide animal reproductive health, and their blood level is reliably associated with reproductive performance. The objective of our research was to determine the effects of supplementation of Vitamin E and mineral mixtures during progesterone treatment on reproductive performance of estrus-induced ewes during the non-breeding season. The present study was carried out between May and June, which is the period accepted as non-breeding season for ewes in Sanliurfa province of Southeast Turkey. A total of 148 non-lactating adult ewes of Awassi breeds in good body score condition, ranging in age from 2 to 4 years and weighting between 45 and 60 kg were used in this study. Estrus was synchronized in all ewes using the intravaginal sponges containing 20 mg fluorogestone acetate. The intravaginal sponges were inserted into vagina of each ewe for 14 days. At the time of sponge withdrawal (day 0), all ewes were injected intramuscularly with 10 IU/kg of PMSG for stimulation of estrus and ovulation. Treatment group (n = 74) received orally supplementation of Vitamin E and mineral mixtures (Bakosel® capsule; Ceva Dif, Istanbul, Turkey; a capsule contains 500 IU Vitamin E acetate, 2.5 mg sodium selenite, 150 mg dicalcium phosphate, 10 mg copper sulphate, 12.5 mg cobalt sulphate) at the four times a week apart during progestagen treatment and at the time mated. The remaining ewes (n = 74) served as control group, and the each female in this group also received only placebo instead of vitamin and mineral supplementation. They were tested for pregnancy detection on day 40 after mating using real time ultrasonography with 5-7.5 MHz linear array rectal transducer. The estrus response was 87.8 % and 82.4 % for the treatment and control groups, respectively. The overall pregnancy rate was 71.4 % (90/126). The gestation length was similar between groups and it averaged 149.4±0.3 days. The lambing rate was 75.4 % (49/65) and 65.6 % (40/61) for the treatment and control groups, respectively. The number of multiple births (42.9 % versus 20.0 %) and prolificacy rate were higher (P < 0.05) for the treatment group than those of control group. It is concluded that Vitamin E and the multi-trace minerals/bolus given to Awassi ewes 14 days before mating significantly increased the proficiency rate, the multiple births rates and led to stronger manifested estrus behaviors.
Keywords: Ewes; PMSG; Pregnant mare serum gonadotropin; Progesterone; Reproductive performance; Trace minerals; Vitamin E